2012
DOI: 10.1534/genetics.112.145516
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Exit and Separation of Mother and Daughter Cells

Abstract: Productive cell proliferation involves efficient and accurate splitting of the dividing cell into two separate entities. This orderly process reflects coordination of diverse cytological events by regulatory systems that drive the cell from mitosis into G1. In the budding yeast Saccharomyces cerevisiae, separation of mother and daughter cells involves coordinated actomyosin ring contraction and septum synthesis, followed by septum destruction. These events occur in precise and rapid sequence once chromosomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(173 citation statements)
references
References 394 publications
(630 reference statements)
3
162
0
5
Order By: Relevance
“…The release becomes definitive following activation of the MEN, and promotes mitotic exit. If the MEN is not activated, CDC14p release is only transient (reviewed by Weiss, 2012). This has some similarity with the unstable SPB association of SIN proteins, particularly GFP-Sid1p.…”
Section: Spatial Instability Of Sin Proteins In the Early Statementioning
confidence: 98%
See 1 more Smart Citation
“…The release becomes definitive following activation of the MEN, and promotes mitotic exit. If the MEN is not activated, CDC14p release is only transient (reviewed by Weiss, 2012). This has some similarity with the unstable SPB association of SIN proteins, particularly GFP-Sid1p.…”
Section: Spatial Instability Of Sin Proteins In the Early Statementioning
confidence: 98%
“…Although the SIN and MEN differ in their 'wiring' (reviewed by Simanis, 2003;Weiss, 2012), this points to a conserved role for Spg1p/TEM1p and Plo1p/CDC5p in regulating the SPB association of Cdc7p family kinases.…”
Section: What Regulates the Early-late Transition?mentioning
confidence: 99%
“…Although the regulatory wiring of the MEN and SIN differ slightly in vegetative cells, previous studies have shown that the regulation of the MEN also differs significantly between meiosis and mitosis. During vegetative growth, MEN signalling originates from the SPB and involves a cascade of protein kinases, the activities of which are modulated by a GTPase (reviewed by Simanis, 2003;Weiss, 2012). By contrast, during meiosis, MEN signalling does not require either SPB association or the scaffold protein used in vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they found that, like the S. cerevisiae ortholog, it plays an important role in mitosis. In S. cerevisiae, Cbk1 plays functions in the mitotic exit network (MEN) and in the regulation of cytokinesis (Weiss 2012). In addition, C. albicans cells lacking components of the RAM pathway show increased levels of multinucleate cells (Song et al 2008).…”
Section: Mitotic Defects Of Mps1 Mutants Are Exacerbated By Loss Of Cmentioning
confidence: 99%
“…Although it has been clearly linked to cell cycle and to daughter cell-specific gene expression (Saputo et al 2012;Weiss 2012), little is known regarding the potential function of the RAM pathway within other pathways that regulate cell morphogenesis and polarity. Our screens identified two genes that interact with CBK1 and are related, or are potentially related, to Cdc42 function.…”
Section: Cbk1 Interacts With Two Genes Related To Cell Polarity Throumentioning
confidence: 99%